Effect of thymoquinone on NRF2 / NF-kB / MAPK pathway in methotrexate-induced rat testis injury - Emin Kaymak; Tayfun Ceylan; Ali Akin; Nurhan Kuloğlu; Meryem Sayan; Necla Değer; Esra Önal; Aysegul Yildirim; Derya Karabulut (Iranian Journal of Basic Medical Sciences)
Objective(s): In this study, we aimed to investigate the protective effect of Thymoquinone (THQ) against testicular damage caused by Methotrexate (MTX).Materials and Methods: This study consists of 5 groups: Control, Olive oil, THQ, MTX, and MTX+THQ. At the end of the experiment, spermiogram analysis was performed on the rats. In addition, testicular tissues were taken and histopathology, immunohistochemistry, and biochemistry analysis were performed. Biochemical analyses were performed on the serums.Results: According to the results obtained, spermiogram values, Johnson’s testicular biopsy score, SOD, CAT, GPx, FSH, LH, and testosterone values were statistically significantly decreased in the MTX group compared to the control group. In the MTX+THQ group, spermiogram values, Johnson’s testicular biopsy score, SOD, CAT, GPx, FSH, LH, and testosterone values increased statistically significantly compared to the MTX group. NRF2 and HO-1 immunoreactivity were statistically significantly decreased in the MTX group compared to the control group. In the MTX+THQ group, NRF2 and HO-1 immunoreactivity were statistically significantly increased compared to the MTX group. The level of MDA, which is important in lipid damage, and the level of biochemistry results of TNF-α, IL1-β, and IL-6, which are important markers, and the results of p-NF-kB and P38 immunoreactivity were statistically significantly increased in the MTX group compared to the control group. In the MTX+THQ group, these parameters showed a significant decrease compared to the MTX group.Conclusion: According to these results, it is thought that THQ will play a protective role against infertility caused by chemotherapy-induced testicular damage.